Trends in Digital Transformation Research in Agribusiness Based on International Publications from 2012 to 2025 - Loso Judijanto; Putu Fajar Kartika Lestari (West Science Agro, 2026)
This study aims to map global research trends on digital transformation in agribusiness based on international publications indexed in Scopus during the period 2012–2025. Using a bibliometric approach and visual analysis through VOSviewer, this research examines publication growth, author and country collaboration networks, institutional linkages, and thematic evolution within the field. The results indicate a significant increase in scholarly output, reflecting growing academic and practical interest in the digitalization of agribusiness systems. Co-authorship and country collaboration analyses reveal strong regional hubs in Europe, Asia, and North America, with emerging participation from developing economies. Keyword co-occurrence and density visualizations identify digital transformation and agribusiness as the central intellectual pillars, closely linked with themes such as artificial intelligence, Internet of Things, precision agriculture, sustainability, food security, and digital economy. Overlay analysis demonstrates a temporal shift from foundational digital infrastructure and economic restructuring toward intelligent, AI-driven applications and smart agriculture systems. The study highlights the interdisciplinary consolidation of digital transformation research in agribusiness while identifying future research opportunities related to governance, digital capability development, inclusivity, and socio-economic impacts.